Accounting and Control for Sustainability: - Songini, Lucrezia; Pistoni, Anna; Herzig, Christian (Emerald, 2013)
Sustainability performance measurement and communication play a central role in supporting the implementation of the sustainability strategy, embedding sustainability into day-to-day operations and decision making, and developing relationships with stakeholders based on trust, transparency, and legitimacy. The purpose of this book is to explore new challenges and new prospects for sustainability accounting research and to discuss future directions of research. It considers a large spectrum of different theoretical lenses and research methods, and explores various types of organizational settings and practices in different countries. This book brings together articles that consider the main areas of accounting: financial accounting, auditing and managerial accounting, in order to critically review and advance theorizations and methodological applications to the study of all main accounting fields in a sustainability context. It aims to interest a quite large number of active researchers, professors and practitioners (CPAs and CMAs, managers and executives, but also consultants), both from the accounting field, and from the sustainability and CSR domains.
Keywords: Social responsibility of business.; Sustainability.; Environmental auditing.; Managerial accounting.; Corporations -- Auditing.; elektronické knihy; electronic books